Digitalization of social infrastructure in left-behind-places: empirical example of schools in Thuringia, Germany - Heßmer, Annika; Schäfer, Susann (Digital geography and society, 2025)
The study of “Left-Behind-Places” (LBPs) in literature has revitalized geographical inequalities across disciplines. In this context, social infrastructure is gaining prominence, with schools being a key component. Schools not only foster education, employment, and community values but also support economic sustainability. Developments in today's society underscore the need of digitalized schools, ensuring schools remain attractive to qualified personnel and highlight their role in developing future potentials. Our case study in Thuringia, Germany, examines digitalization, location factors, and personnel qualifications at public schools using a standardized questionnaire, providing insights into regional disparities and their impact on LBPs.
Gesehen am 05.06.2025
Online veröffentlicht: 31. März 2025